ASSESSMENT OF RISK FACTORS FOR THE DEVELOPMENT OF BRONCHO-OBSTRUCTIVE SYNDROME IN CHILDREN - L.A. Mukhamadieva,; Ogabek Khaydarov, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ABSTRACT   Background: Broncho-obstructive syndrome (BOS) is a common complication of acute lower respiratory diseases in children and is associated with an increased risk of bronchial asthma.   Objective:  To  identify  and  systematize  risk  factors  contributing  to  the development of BOS in children with acute obstructive bronchitis (AOB).   Methods: A retrospective cohort study included 912 children aged 2 months to 5 years hospitalized from 2012 to 2015. Group 1 consisted of 494 children with BOS on the background of AOB, while Group 2 included 418 children with acute bronchitis without obstruction. Statistical analysis was performed using Pearson’s chi-square (χ²) test.   Results: Among 49 identified factors, 28 were statistically significant. Major risk factors included male gender, older age, allergic predisposition, atopic dermatitis, thymomegaly, passive smoking, early artificial feeding, and seasonal factors (winter and  spring).  Predisposing  factors  included  frequent  respiratory  infections,  rickets, prematurity, adverse environmental conditions, and delayed medical care.   Conclusion: BOS development in children is multifactorial. Identification of modifiable  risk  factors  enables  early  prevention  and  reduces  the  likelihood  of progression to bronchial asthma.